Knowledge, attitudes and perceived barriers to emergency contraception among health staff in a tertiary hospital in Yaounde, Cameroon - Fouedjio, Jeanne Hortence; Fouogue, Jovanny Tsuala; Fouelifack, Florent Ymele; Mout, Valerie Ngankol; Fouelifa, Loïc Dongmo; Sando, Zacharie (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Unsafe abortion is a scourge worldwide. In Cameroon, modern contraceptive prevalence is 16%, with unmet need of 25%. Knowledge and attitudes of health staff toward emergency contraception (EC) are unknown. The aim of this study was to assess knowledge, attitudes of health staff towards EC and determine barriers they perceived to its popularization. Methods: A descriptive cross-sectional study was carried out in a tertiary Hospital from April 1, to June 30, 2015 on a convenient sample of 150 health workers. All the staff present in the facility on the day of the survey was eligible. A pre-tested and anonymous questionnaire was distributed to 150 health staff. Data were analyzed using SPSS® software. Results: The response rate was 78.7% (118/150). Mean age was 34.7 ± 8.8 years and 94.9% (112/118) of respondents were Christians. The mean number of children per respondent was 2.5 ± 1.6 and the mean duration of professional experience was 6.9 ±6.6 years. Eighty nine (75.4%) respondents were women and sixty (50.8%) were nurses. Awareness was good (87.5%), but knowledge was insufficient for 44.1% (52/118) and poor for 11.9% (14/118) of respondents. Attitudes towards EC were appropriate for 44.6% (46/103) of respondents. Eighty percent of respondents were not satisfied with their knowledge and 90.4% requested training on EC. Perceived barriers were: promotion of precocious (82.9% of respondents) and unprotected (75.4%) sex, side effects (70.6%), liability (47.7%) and ethical/religious (42.2%) principles. Conclusions: Knowledge and attitudes of health staff towards EC was inadequate. Promotion of precocious and unprotected sex was the main perceived barrier to EC. Health staff needs training on EC.